Pengaruh Kombinasi Jarak Tanam dan Varietas terhadap Pertumbuhan dan Hasil Tanaman Jagung (zea mays l.) di Loes, Sub District Maubara, District Liquisa Repupublica Democratica De Timor Leste - MANUEL PATRICIO XIMENES; IDA AYU MAYUN; NI LUH MADE PRADNYAWATHI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2018)
The Combined Effect of Plant Spacing and Varieties on the Growth and the Corn Yields (zea mays l.) at Loes, Sub District of Maubara, District of Liquisa Repupublica Democratica De Timor Leste Plant spacing will affect the density of plant, efficiency of light use, the competition of plants in the use of water and nutrients, and finally will affect the production of plants. Each variety of corn crops requires planting distance suitable for optimal growth and maximum yield. This study aims to determine the best combination of plant spacing and corn varieties in yielding optimal growth and highest yield. The study used Randomized Block Design (RAK) with nine treatments and three replications. The experimental treatments were: a combination of plant spacing of 50 cm x 40 cm and Sele varieties; combination spacing of 50 cm x 40 cm and Noimutin varieties; combination of plant spacing of 50 cm x 40 cm and Nai varieties; combination spacing of 75 cm x 25 cm and Sele varieties; combination spacing of 75 cm x 25 cm and Noimutin varieties; combination spacing of 75 cm x 25 cm and varieties of Nai; combination spacing of 80 cm x 25 cm and Sele varieties; combination spacing of 80 cm x 25 cm and Noimutin varieties; and the combination of plant spacing of 80 cm x 25 cm and Nai varieties. The results showed that the combination of plant spacing of 75 cm x 25 cm and Nai varieties produced the best growth of corn plants, with the highest leaf area (286.35 cm2) and the highest stem diameter (2.787 cm). The highest dried seeds of 13% were found in the same treatment with an average value of 149.60 g per plant and 7.78 tons per hectare.